A Continuous Model for Demand‐Side Management in an Aggregator Model in Electricity Markets. Issue 1 (24th March 2023) - Thünen, Anna; Ulke, Alena
Abstract: We develop a novel time continuous Stackelberg game to model the interaction of costumers and aggregators in electricity markets. It features time dependent pricing policies that aim to align electricity consumption with its availability. Furthermore the model has the special potential of scalability with respect to the amount of costumers. We illustrate that in fact the aggregator can create an incentive to the costumer that is then changing its consumption behavior.